The effect of the timing of umbilical cord clamping on hemoglobin levels, neonatal outcomes and developmental status in infants at 4 months old - Nouraie, Soheila; Amir Ali Akbari, Sedigheh; Vameghi, Roshanak; Akbarzade Baghban, Alireza (Iranian Journal of Child Neurology, 2019)
Objective: Delayed umbilical cord clamping (DCC) increases blood transfer to newborns. Hence we investigated the effect of the timing of DCC on hemoglobin levels, neonatal outcomes and developmental status in infants at four months old . Materials & Methods: This clinical trial examined infants born to 400 pregnant women immediately upon birth and at the age of four months. The newborns were randomly assigned to either the intervention group with a 90-120-second delay in umbilical cord clamping or the control group with a clamping delay of below 60 seconds, and blood samples were taken from their umbilical cords. The Ages and Stages Questionnaire was used to evaluate the infants’ developmental status. Results: Umbilical cord hemoglobin was found to be significantly higher in the intervention group compared to in the controls (P=0/024). No significant differences were observed between the two groups in terms of neonatal complications except neonatal jaundice was significantly more common in the intervention group (P=0/025), although the need for phototherapy was not different between the groups. Overall, no significant differences were observed between the two groups in terms of developmental status at four months old; however, the infants had better problem-solving skills in the delayed umbilical cord clamping group (P=0/015). Conclusion: The results obtained show that, despite elevating hemoglobin, delayed umbilical cord clamping but has no effects on infant development except in terms of problem-solving skills. Further studies are recommended on the effects of delayed umbilical cord clamping on infant development.